Child Development and Parental Investment: Introduction. (7th December 2016) - Francesconi, Marco; Heckman, James J.
Abstract : This article introduces the EJ Feature on Child Development by reviewing the literature and placing the contributions of the articles in the Feature in the context of a vibrant literature.